Optimasi Moringa Gum dan Hidroksi Propil Metil Selulosa dalam Sediaan Mucoadhesive Buccal Film Diltiazem Hidroklorida - Sari, Lusia Oktora Ruma Kumala; Hanif, Mohammad Ainul Fakhruddin; Irawan, Eka Deddy; Winarti, Lina; Barikah, Kuni Zu’aimah; Rosyidi, Viddy Agustian; Eryani, Mikhania Christiningtyas; Febryanto, Hery Diar (Faculty of Pharmacy, University of Jember, 2025)
Moringa gum is a natural polymer obtained from Moringa oleifera plant and has been used as a stabilizer, binder, disintegrant, and controlled release matrix. Moringa gum has a polyuronide group, which can potentially be a mucoadhesive agent. This study used moringa gum as a mucoadhesive agent in diltiazem HCl mucoadhesive buccal film. This research aimed to determine the effect of the combination of moringa gum and HPMC on surface pH, swelling index, and in-vitro mucoadhesive residence time. Mucoadhesive buccal films were evaluated for weight and thickness uniformity, folding resistance, drug content, surface pH, swelling index, in-vitro mucoadhesive residence time, and characterization in the form of FTIR and release studies. All formulations met the tests of uniformity of weight and thickness, folding resistance, and drug content. The results showed FB as the optimum formula with a surface pH of 5.803±0.101, a swelling index of 7.031±0.134, and a residence time of 505.67±4.51 minutes. FTIR showed no interaction, and the release study showed 82.197±1.178% release at 480 minutes. In conclusion, a combination of moringa gum and HPMC mucoadhesive buccal film has been successfully prepared with moringa gum as a mucoadhesive agent that increases the residence time.